2021
DOI: 10.1016/j.tvr.2021.200221
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 and HPV18 type-specific APOBEC3 and integration profiles in different diagnostic categories of cervical samples

Abstract: Human papillomavirus (HPV) 16 and 18 are the most predominant types in cervical cancer. Only a small fraction of HPV infections progress to cancer, indicating that additional factors and genomic events contribute to the carcinogenesis, such as minor nucleotide variation caused by APOBEC3 and chromosomal integration. We analysed intra-host minor nucleotide variants (MNVs) and integration in HPV16 and HPV18 positive cervical samples with different morphology. Samples were sequenced using an HPV whole … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 62 publications
(107 reference statements)
7
22
0
Order By: Relevance
“…However, this decrease is not observed in HPV31 and HPV33 positive samples, suggesting this is not an Alpha-9 specific tendency, but rather a feature of HPV16 carcinogenesis. Our results are in corroboration with previous studies that have observed that the number of APOBEC3-related nucleotide substitutions decreases with lesion severity in HPV16 positive samples [ 17 , 20 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, this decrease is not observed in HPV31 and HPV33 positive samples, suggesting this is not an Alpha-9 specific tendency, but rather a feature of HPV16 carcinogenesis. Our results are in corroboration with previous studies that have observed that the number of APOBEC3-related nucleotide substitutions decreases with lesion severity in HPV16 positive samples [ 17 , 20 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Yet, contrary to current understanding it cannot be established that APOBEC3-induced mutagenesis in viral genomes is a general detectable feature in high-risk HPV infections. In HPV16 positive samples, the number of APOBEC3-related nucleotide substitutions decreases with lesion severity, which also has been shown in previous studies [ 17 , 20 , 43 ]. However, this decrease is not observed in HPV31 and HPV33 positive samples, suggesting this is not an Alpha-9 specific tendency, but rather a feature of HPV16 carcinogenesis.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations